Analisis Stock Split Terhadap Harga Saham PT Jaya Real Property Tahun 2010-2016 - Ina Novitasari; Dwi Budiadi; Arthur Daniel Limantara (CAHAYA AKTIVA, 2020)
Stocks with low levels of sale can be explained because the stock price itself is too high.There are some efforts done by the company in preventing stock splitting with the aim of lowering the stock price and also having the main objective to attract investors to investors to liquidate the company's shares. Research on stock splitting (stock split) has been done several times but it gives different results. Then needs further research.Research was conducted at PT Jaya Real Property Tbk in 2010-2016 which carried out a stock split and did not carry out any other policy than stock split. Determination of the sample using purposive sampling. This study uses a different test analysis using the Paired Sample T-Test to find out whether there is a significant difference in the price of shares before and after the stock split Test results of the Paired Sample T-Test before and after the stock split of stock prices prove a drastic difference.Keywords: Stock split ,Pared Sample T-Test test